Inducible forward programming of human induced pluripotent stem cells to skeletal myocytes - Löfgren, Emil (My University, 2024)
Differentiation of human induced pluripotent stem cells into a desired phenotype is challenging. Previous attempts of hiPSC differentiation into skeletal myocytes using an in-house protocol has resulted in heterogeneous populations of cells. Resolving the heterogeneity of Skeletal myocyte differentiation is key for acquiring tissues and cell types suited for exploring novel therapies and mechanisms within muscle related diseases. Thus the main objective of this thesis was to investigate if alterations in gene expression could resolve the heterogeneity of the differentiation process of Skeletal Myocytes. In this thesis, differentiation of hiPSCs into skeletal myocytes was explored through modulation of the transcription factors MYOD1 and OCT4 using the genome editing enrichment method "Xential". The addition of the HBB IVS2 intron sequence led to a 2-fold increase in MYOD1 expression, furthermore adjustments to the seeding density led to an additional 2- fold increase of MYOD1. Knockdown efficiency of shRNA targeting POU5F1 is correlated with the seeding density. The downstream marker of myogenesis DES had a 15-fold increase when seeding density was adjusted. This correlation between differentiation efficiency and seeding density highlights the interplay between envi- ronmental pressures and gene expression. The HBB IVS2 intron sequence led to higher homogeneity in the cultures, this provides insights into future strategies to mitigate heterogeneity in hiPSC differentiation.
Keywords: Skeletal Myocytes; hiPSC; iPSC; MYOD1; OCT4; Seeding Density; Xential; Diphtheria Toxin; differentiation; HBB ISV2